Answer:
(4,-3)
Step-by-step explanation:
Multiplying the bottom equation by -6, we get -6x+12y=-60.
Adding this to the first equation gives 15y=-45, and thus y=-3.
So, it follows that 6x+3(-3)=15, and thus x=4.
1) -x + 4 = -2x - 6
Add(2x)
x+4=-6
Subtract(4)
x = -10
<u>Check your work</u>
-(-10)+4=-2(-10) - 6
10+4=-2(-10) - 6
14=-2(-10)
14=20 - 6
14=14
Correct :)
2) 4R - 4 = 3R + 10
Add 4
4R=3R+14
Subtract 3R
R = 14
<u>Check your work</u>
4(14)-4=3(14)+10
56-4=3(14)+10
52=3(14)+10
52=42+10
52=52
Correct :)
3) 2Y - 3 = Y - 4
Add 3
2Y = Y - 1
Subtract Y
Y = -1
<u>Check your work</u>
2(-1)-3=-1-4
-2-3=-1-4
-5=-5
Correct :)
<em>Hope it helps <3</em>
Answer:
Step-by-step explanation:
A(-6,2) =>A'(-5, -1)
B(-5,4) =>B'( -4,1)
C(-2,4)=> C'(-1,1)
D( 1,2) => D'(2,-1)
we move all these points to (x+1, y-3)
A=a+b+c+d/4
subtract a from both sides
0=b+c+d/4
Subtract b from both sides
-b=c+d/4
Finally subtract d/4 from both sides
c=-d/4-b
Answer:
idk sorry
Step-by-step explanation: